2014
DOI: 10.5194/bg-11-4477-2014
|View full text |Cite
|
Sign up to set email alerts
|

The implications of microbial and substrate limitation for the fates of carbon in different organic soil horizon types of boreal forest ecosystems: a mechanistically based model analysis

Abstract: Abstract. The large amount of soil carbon in boreal forest ecosystems has the potential to influence the climate system if released in large quantities in response to warming. Thus, there is a need to better understand and represent the environmental sensitivity of soil carbon decomposition. Most soil carbon decomposition models rely on empirical relationships omitting key biogeochemical mechanisms and their response to climate change is highly uncertain. In this study, we developed a multi-layer microbial exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…The heterogeneous distribution of SOC and its bioavailability due to local physical protection and chemical recalcitrance (Six et al 2002), preferential and matrix transport of substrates due to pore connectivity and local moisture content (Hunt 2004;Liu et al 2015aLiu et al , 2014Steefel and Maher 2009), and nonuniform formation of microbial colonies and biofilms due to local substrate availability and predation inhibition (He et al 2014;Kakumanu et al 2013;Or et al 2007;Xu et al 2014) have been observed to affect the rate of heterotrophic respiration and its correlation with moisture content in soils (Franzluebbers 1999;Moyano et al 2012). Understanding the pore-scale physical and biochemical processes associated with these heterogeneous properties as well as their manifestations at large scales is crucial to reduce the uncertainty of predicting the relationship between HR rate and moisture content in soil systems.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous distribution of SOC and its bioavailability due to local physical protection and chemical recalcitrance (Six et al 2002), preferential and matrix transport of substrates due to pore connectivity and local moisture content (Hunt 2004;Liu et al 2015aLiu et al , 2014Steefel and Maher 2009), and nonuniform formation of microbial colonies and biofilms due to local substrate availability and predation inhibition (He et al 2014;Kakumanu et al 2013;Or et al 2007;Xu et al 2014) have been observed to affect the rate of heterotrophic respiration and its correlation with moisture content in soils (Franzluebbers 1999;Moyano et al 2012). Understanding the pore-scale physical and biochemical processes associated with these heterogeneous properties as well as their manifestations at large scales is crucial to reduce the uncertainty of predicting the relationship between HR rate and moisture content in soil systems.…”
Section: Introductionmentioning
confidence: 99%
“…This has been manifested in a long list of microbial models that were published in the last few years (e.g., Schimel and Weintrub, 2003;Moorhead and Sinsabaugh, 2006;Allison et al, 2010;German et al, 2012;Wang et al, 2013;Wieder et al, 2013;Li et al, 2014;He et al, 2014;Riley et al, 2014;Xenakis and Williams, 2014;Tang and Riley, 2015;Sulman et al, 2014;Wieder et al, 2015). To build a microbial model, the substrate kinetics is fundamental as it describes the rate at which microbes would take up a substrate and represents the first step towards describing how microbes would decompose the soil organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…Factors in addition to substrate quantity can limit heterotrophic metabolism (catabolism, anabolism, or both), including substrate quality (Jagadamma et al, 2014), mode and timing of substrate production (Carlson, 2002; Jiao et al, 2010), temperature (He et al, 2014), nutrient availability (Morita, 1997), and, in terms of the energy available from metabolic reactions, the redox environment (Brewer et al, 2014). We discuss these below.…”
Section: Discussionmentioning
confidence: 99%